On the Hypergraphs and candidate keys - Thi, Vu Duc (Journal of Computer Science and Cybernetics, 2016)
The combinatorial problems are interesting in the relational datamodel. The theory of hypergraphs was a very useful tool for the solution of combinatorial problems. The transversal and the minimal transversal are important concepts in this theory. In this paper, base on hypergraph we give some new characterizations of the set the candidate keys in the relational datamodel.